Perception of quality of life at work in a secretariat of the Federal District Government (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: Quality of Life at Work (QLW) can provide benefits for personal and professional life,  as well as generating conditions for greater productivity and organizational effectiveness.Purpose: Identify the perception regarding the quality of life at work in a Secretariat of the Government of the Federal District,  as well as verifying whether there is a difference in perception between managers and employees of the organization and in people who participated in quality of life actions offered by the organization.Method: The quantitative research, in a non-probabilistic convenience sampling, obtained a sample of 291 civil servants of a GDF Secretariat who answered an electronic questionnaire to evaluate, using a Likert scale, 35 items grouped into 10 QLW dimensions, in addition to profile questions. Results: Only 49.3% indicated a degree of agreement  in having QLW. The dimensions of telework and opportunity to use and develop capabilities were the best evaluated, and fair and adequate compensation as well as chance of growth and job security were the worst evaluated. There is no significant difference regarding occupation of management positions in the QLW dimensions, and there is a significant difference except in the dimension of QLW in general of those who participated in the QLW program.Conclusions: The study corroborates findings from the literature on research in public organizations regarding the most satisfactory and unsatisfactory dimensions of the QLW      model, highlights the need to adopt teleworking in the organization to improve the QLW      of      civil servants, and indicates the relevance of public organizations investing in QLW programs. The article contributes by advancing group comparison studies, in studying the perception of QLW in public organizations. A diagnosis   that can be useful for public organizations was presented, when establishing their quality of life programs at work.